The Ability of Digital Literacy for Elementary School Teachers - Berliana Hutagalung; Widyastuti Purbani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to analyze the digital literacy skills of elementary school teachers. This study used quantitative research. The research subjects were 76 elementary school teachers. The research instruments used were observation sheets, interview guides, and questionnaires. The data analysis technique used in this research is a descriptive statistical analysis which is carried out by providing an overview of the data that has been collected and then making conclusions or descriptions related to the data. Based on the results of this study, it can be seen that the digital literacy skills of elementary school teachers need to be improved. This is done so that elementary school teachers can have good literacy skills in using and utilizing existing technology tools and digital media to design or design learning processes that are creative, innovative, and fun and can make students think critically. Also, good digital literacy skills can help teachers respond to the challenges of the times related to the application of mixed learning models in the world of education. A good teacher's digital literacy skills can help teachers transform learning so that it is more creative, innovative. Also, teachers can answer the challenges of the times related to the application of blended learning. A teacher who has good digital literacy skills shows that the teacher has a desire to continue to learn and develop his professional teaching.